European food composition tables in translation - Arab-Kohlmeier, Lenore; Wittler, Marion; Schettler, Gotthard (Veröffentlichungen aus der Geomedizinischen Forschungsstelle der Heidelberger Akademie der Wissenschaften, Supplement zu den Sitzungsberichten der Mathematisch-naturwissenschaftlichen Klasse Jahrgang 1987, 1987)
The limited resources available for chemical analyses of components of interest in food has forced scientists to borrrow data from published food composition works of other countries. Due to language barriers, this is often undertaken without due knowledge of the background and instructions for use. This book contains English-language translations of the introductory material and guidelines for use included in the most recent editions of 21 published food composition tables of 14 European countries. It has been compiled with the assistance and cooperation of many collaborators throughout the world. This information is meant to help scientists referring to foreign food tables have a better understanding of the information they are using and to help prevent misuse and undue comparison